Collectie Vlaamse Gemeenschap aanwinsten 2002-2006 - Cornelis, Jef; Bert, Evi; De Boeck, Jo; Coulembier, Johan (Brussel : Vlaamse overheid: Kunsten en Erfgoed, 2008)
Ensor, James ; Panamarenko ; Broodthaers, Marcel ; Augustijnen, Sven ; Alys, Francis ; Bijl, Guillaume ; Buggenhout, Peter ; Catrysse, Wim ; Colson, Vaast ; Daems, Anne ; de Boeck, Lieven ; de Boer, Manon ; De Clercq, Anouk ; De Gruyter, Jos ; Thys, Harald ; Dockx, Nico ; Luyten, Mark ; Dujourie, Lili ; François, Michel ; Venlet, Richard ; Goiris, Geert ; Grimonprez, Johan ; Michiels, Stan ; Oorebeek, Willem ; Opsomer, Els ; Swennen, Walter ; 't Jolle, Sven ; Torfs, Ana ; Van Caeckenbergh, Patrick ; Van Kerckhoven, Anne-Mie ; Vercruysse, Jan ; Vermeire, Katrien ; Tiong Ang ; Villevoye, Roy ; Ataman, Kutlug ; Bar-El, Ido ; Braeckman, Dirk ; Bratkov, Sergey ; Colson, Vaast ; Curlet, François ; De Vree, Paul ; Filliou, Robert ; Fishkin, Vadim ; Leiderman, Yuri ; Fraser, Andrea ; Geys, Jef ; Gygi, Fabrice ; Horn, Roni ; Kandl, Johanna ; Kempenaers, Jan ; Kinoshita, Suchan ; Kippenberger, Martin ; Kunuk, Zacharias ; Langa, Moshekwa ; Lewis, Mark ; Yue Liang ; Matta-Clark, Gordon ; Matthys, Danny ; Mees, Guy ; Monroe (Vladislav Mamyshev) ; Ninio, Moshe ; Pacquée, Ria ; Pistoletto, Michelangelo ; Robijns, Gert ; Sasnal, Wilhelm ; Sumnin, Andrei (Monastyrski) ; Swennen, Walter ; Tersas, Toon ; Thauberger, Althea ; Tuymans, Luc ; Van Damme, Caroline ; Vergara Santiago, Angel ; Visser, Barbara ; West, Franz ; Williams, Emmett ; Aguirre y Otegui, Philip ; Bervoets, Fred ; Geelen, Guido ; Delrue, Ronny ; Denmark ; Eisinga, Jeroen ; Framis, Alicia ; Frize, Bernard ; Janssens, Ann Veronica ; Kobayashi, Masato ; de Beeck, Hans Op ; Van Imschoot, Jan ; Van Kerckhoven, Anne-Mie ; van Warmerdam, Marijke ; Claus, Filip ; Houben, Gilles ; Iglesias, Cristina ; Sanders, Jan
boek